Potenrammen als rite de passage : daders van anti-homoseksueel geweld in beeld. - van der Meer, Theo; van den Boogaard, Henk (Amsterdam : SAD-Schorerstichting NISSO, 1995)
Fonds Suzan Daniel (FSD)
Scriptie
Nederlands
Monografie